Srpski - Kovač, Kristian Z (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2026)
The relationship between the breach of an international treaty and the use of force appears to be undisputed – contemporary international law leaves no room for invoking a treaty breach as an independent legal basis for the use of force. However, through selected case studies, this paper explores how states invoke treaty breaches within their legal arguments when justifying the right to self-defence as one of the exceptions to the prohibition of the use of force. Furthermore, the paper analyzes whether a breach of an international treaty is utilized by the United Nations Security Council as an argumentative element when authorizing the use of force, representing the second exception to the general prohibition. The subject of consideration includes the regime of the prohibition of the use of force, the provisions of the law of international treaties, and the rules on the responsibility of states for internationally wrongful acts. Finally, the paper examines the doctrinal debate between extensive and restrictive interpretations of the right to self-defence, specifically addressing whether a treaty breach can serve as a "trigger" for the activation of this right.
Keywords: State responsibility for internationally wrongful acts; breach of international treaties; United Nations Security Council; right of self defence; prohibition of the use of force